From Microenterprise to Market Leadership: A Case Study of Fruit Crisp Industry in East Java, Indonesia. - Augendra Bhukuth; Qausya Faviandhani; Ani Wulandari (International Journal of Small and Medium Enterprises and Business Sustainability, 2024)
This paper presents a case study of a fruit crisp industry in East Java, Indonesia. A successful journey of an entrepreneur who has started his business from a micro level to become a market leader in the industry is analyzed. The entrepreneur has implemented different strategies to become a leader. The entrepreneur started by controlling the fruit supply and prices in the fruit market, he implemented a strategy of product differentiation. He produces dry food machines, subcontracts fruit crisps, and is involved in packing and fruit crisp distribution.